The Effect of Great Indonesian Children's Gymnastics on Children's Motor Movement Skills in Physical Education Learning in Elementary School - wiguno, Lokananta Teguh Hari; Isnaini, Lalu Moh Yudha; Rusdiyanto, Rajip Mustafillah; Irmansyah, Johan (Universitas Hamzanwadi, 2025)
Motor movement skills are an important foundation in the physical and cognitive development of elementary school-age children. However, physical education learning in many schools is still less than optimal in developing the motor aspects as a whole through an approach that is in accordance with the characteristics of the child. This study aims to examine the influence of the great Indonesian Children's Gymnastics program on the motor movement ability of elementary school students. The method used was a experiment with a Pretest-Posttest Design with Control Group, involving 60 students in grades IV and V in one of the public elementary schools in Malang district. Motor ability measurement is carried out through four aspects: running, balance, agility and leg muscle strength. The results of the paired sample t-test showed a significant improvement in all aspects of motor movement after participating in the great Indonesian children's gymnastics program (p < 0.05). However, the level of significance indicated only a modest effect size, suggesting that the impact, while meaningful, was relatively small. These findings suggest that movement-based gymnastics designed in a fun and structured manner can contribute to the improvement of children's motor skills, although further refinement of the program may be needed to achieve stronger outcomes. This study concludes that Great Indonesian Children’s Gymnastics can serve as an alternative learning strategy in elementary schools to support motor development, but its effectiveness requires further optimization.